Shape Memory Polymer-Based Nanocomposites Magnetically Enhanced with Fe3O4 Nanoparticles - Pekdemir, Mustafa Ersin; Aydin, Derya; Pekdemir, Sibel Selcuk; Sonmez, Pinar Erecevit; Aksoy, Edanur (Springer, 2023)
This work aimed to investigate the effect of magnetic Fe3O4 nanoparticles (MNP), which are known to have a wide range of applications in recent years, on nanocomposite films prepared with shape memory polymers. Herein, PLA-PEG blend nanocomposite films were prepared by solution casting method using MNP at different ratios. PLA-PEG Blend/MNP nanocomposite films were characterized with Attenuated total reflection infrared spectroscopy (ATR-IR) to determine the -C=O stretching of PLA and Fe-O stretching signals of Fe3O4. The thermal stability, morphology, and magnetic behavior were studied by comparing the results among PLA-PEG blend, PLA-PEG blend/MNP nanocomposite with thermogravimetric analyses (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and a vibrating sample magnetometer (VSM), respectively. The effect of MNP on the shape memory properties of PLA/PEG blend was investigated. Moreover, the comparison of antimicrobial activity between PLA/PEG blend and PLA-PEG blend/MNP nanocomposite films were conducted by the disk diffusion method. The results showed that MNP increased the thermal stability of the PLA/PEG blend and the nanocomposites inhibited the growth of C.albicans microorganism.
Keywords: Magnetic nanoparticle; polymer blend; nanocomposite; shape memory; antimicrobial